Przestrzenna dyslokacja ośrodków władania - Ławniczak, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
For each statehood a capital is something important. In the original, simplified version, where there is a Chief of State, there is a capital. So when a Monocrat travels, the political centre of state moves with him. This paradigm changes with the progress of modernity. Elephantiasisof the post-medieval state can be seen in the process of the growing number of clerks. They, being concentrated in an agglomeration governing class, de facto have a ruling position in statehood even in the situation of the King’s absence in the capital. In the post-revolutionary period the situation changed. We observe the appearance of republican federations with many sub-capitals. On the other hand, the realization of Lockean-Montesquian Dogma has an effect in the phenomenon of geographical separation, in any countries, centers of parliamentary, executive and judicial powers. Still, it is no time for the End of History. So, probably, in the period of the eventual future New Time, an ex novo new generation of humankind shall be the witness of the radical centralization of human power in statehood as the effect of Great Wave regularity in the long historical perspective.
Keywords: stolica; państwowość; dyslokacja; władza